СТВОРЕННЯ АКТИВНО-ТВОРЧОГО КЛІМАТУ НА МЕТОДИЧНИХ ЗАНЯТТЯХ ДЛЯ РОЗВИТКУ ТВОРЧОГО СТИЛЮ ДІЯЛЬНОСТІ ПЕДАГОГА (Педагогіка вищої та середньої школи, 2003)
In the article is concretized such conception “climate”, “activity” and the characteristic is given for active-creative climate, the meaning of creationih live creative climate at the methodic lectures is reveated, the process of creating the work, the teachers results of creative group auproposed and checked.